PENGARUH KOMPOSISI CU-ZN TERHADAP TINGKAT KEKERASAN DAN STRUKTUR MIKRO ALUMINIUM DIE CASTING (ADC) 12 SEBAGAI BAHAN PROPELLER - Ahmad Ilham Ramadhani; Barokah Barokah; Fahriadi Pakaya; Jozua Ch. Huwae; Marinus S. Tappy; Andie Murtono; Ahmad Tubagus Tsani Risqi Aji (JURNAL BLUEFIN FISHERIES, 2022)
Propeller is one of the important components of a ship. Generally, propellers are made of aluminum which is easily damaged when hit by waves and corrosion. The development is done by adding brass (Cu-Zn) on ADC 12. The sample was successfully made with a ratio of 70% ADC 12 : 30% Cu-Zn using the casting method and then cooled at room temperature followed by die casting and sand casting processes. The sample was tested for hardness using the Rockwell method according to the ASTM E18 standard and the microstructure test on the sample. Based on the test results obtained an average hardness level of 72.6 HRC and the formation of Al-Si-Mg, α-Al, Cu, Zn in the sample which shows the distribution of non-ferrous material in ADC-12. Keywords : ADC 12; Cu-Zn; propeller; microstructure; hardness